A DNA-binding, albumin-targeting fusion protein promotes the cellular uptake and bioavailability of framework DNA nanostructures. Issue 12 (19th March 2021) - Li, Xue; Xu, Fan; Yang, Donglei; Wang, Pengfei
Abstract : A fusion protein is designed to tether onto framework DNA nanocarriers to aid the recruitment of serum albumins for enhanced biological performances. Abstract : Framework DNA nanostructures exhibit unique characteristics such as precisely controllable physicochemical properties ( i.e. size, shape, and surface functionality) and have been used as carriers for the delivery of a variety of therapeutics. Nevertheless, pristine DNA nanostructures encounter challenges such as low cellular uptake efficiency and short in vivo retention time that largely hinder their biomedical applications. Here in this report, a fusion protein is designed to complex with a tetrahedral DNA nanostructure (TDN) to circumvent these challenges by recruiting serum albumins. This bi-functional fusion protein (ABS) is composed of an albumin-binding domain (ABD) and a DNA-binding domain (Sso-7d), which can serve as a linker to bridge the TDN with albumin. It was revealed that ABS-tethered TDN can readily recruit serum albumins to achieve significantly enhanced uptake in cancer cells and longer retention time in mice, suggesting that ABS may serve as a potent agent to facilitate the biological applications of DNA nanostructures.